Conceptual knowledge and sensitization on Asperger's syndrome based on the constructivist approach through virtual reality - Hadjipanayi, Christos; Michael-Grigoriou, Despina (My University, 2020)
© 2020 The Authors The immense capabilities provided by virtual reality for enhancing empathy and altering social behaviors, make it possible to use virtual reality for the promotion of the understanding between individuals. A social issue that needs to be addressed is the discrimination and marginalization of people with Asperger's syndrome (AS) from the working force, stemming from the lack of recognition and justification of their oddities. In this paper, the effectiveness of a virtual reality simulation, raising awareness on this specific issue, is evaluated. Awareness is a term used in this research to refer to the combination of conceptual knowledge and sensitization on a specific issue. An experiment with between-group design has been carried out, where half of the participants used the simulation via a VR headset device and the other half was given a transcript of relevant medical articles instead. The comparison between the two groups indicates that the group which used the simulation gained more knowledge on AS than the group which used the transcript. Moreover, the parameter of sensitization indicates positive correlations with place illusion in the VR group.
Keywords: Asperger's syndrome; Computer in education; Computer science; Constructivist approach; Empathy; Human machine interaction; Human-centered computing; Mental health; Neuroscience; Psychological disorders; Psychology; Social sciences; Virtual reality; VR illusions; Well-being